Expertise in the criminal judicial process - Buzescu, Gheorghe (Technium Social Sciences Journal, 2024)
Only on the basis of the exact establishment of the factual circumstances of the case, the judicial team can resolve the respective case, applying the provisions contained in the law on liability for such a situation. The judicial team will pronounce, thus, a sound and legal decision, a convincing decision both for the parties in the process and for those outside, this is necessary to ensure the preservation of legality and by law. The experts, as means of proof are used by the judicial bodies in those cases in the salt, to foresee some facts, to establish the southern connection between them, are necessary special knowledge in the field first, techniques or arts. It is not possible for the judicial team to be a specialised in all matters, and even a more complete general training could not (at this stage of development of science and technology) equally cover the the field, in all its aspects. To this it is necessary to add that in some situations a special effort is required, as a rule, it cannot be done outside the court or only with the help of some technical means. The necessity of using experts is so obvious, but it cannot be denied. More than that, it was argued that even in the case where the court would have a specialist, such a situation cannot eliminate the need to call in experts, even though the judge and the expert have the functions of the process other differences. On the other hand, the utility of using this means of evidence in the activity of the judicial team is reflected in laws and other such regulations, the legislator itself providing for the obligation to resort to expertise in certain situations. At the same time, the establishment of some state institutions intended for this purpose, the election of experts from among the specialists and the higher salification, clearly demonstrates the importance of the institution. The emphasis made in the preceding lines regarding the importance of these means of evidence and scientific evidence, should be understood in the sense that the expert’s opinion does not have absolute probative force, being subject to freedom of expression of the judicial body in the light of his legal conscience and according to his conviction. Although the expertise is not decisive in resolving a dispute, it does not oblige the judicial body to give a certain solution, and only gives it the possibility to form its own opinion. It is obvious, however, that given the basis of the scientific argument of the opinion expressed by the expert, the rejection of the expert’s conclusions on the grounds that they would not be convincing or the maintenance of these conclusions, although to remove one or all parts of the process, it will have to be motivated and special care.